(untitled) (Research, Society and Development, 2020)
The aim of the study was to analyze the quality indicators in enteral nutritional therapy in patients admitted to an intensive care unit (ICU) of a trauma reference hospital. For this purpose, a retrospective observational study was carried out with patients aged ≥18 years, who received exclusive enteral nutritional therapy for at least 72 hours in the ICU, from May to September 2017. Demographic data, medical diagnosis, time to start infusion of enteral nutrition, information on prescribed versus infused nutrition, number of patients reaching 50%, 70% and 100% of energy and protein in three, five and seven days, respectively, were collected, in addition to gastrointestinal symptoms present during enteral nutritional therapy. Data from 96 patients were eligible. It was observed that 77% the sample was hospitalized due to trauma and 11.34% had a fasting frequency greater than 48 hours. The adequacy of the volume of infused versus prescribed nutrition was 83.42%. Only 44.8% of patients reached 50% of the recommended energy in 3 days, while 57.2% reached 70% in 5 days and 44.2 reached 100% in 7 days. As for protein intake, 46.9% reached 50% of the recommended intake within 3 days; 57.2% reached 70% in 5 days and 41.5% reached 100% in 7 days. The frequency of gastrointestinal symptoms was 44.7%. Approximately half of the sample did not progressively reach the desired energy and proteins percentages. It is recommended to monitor the nutritional evolution, identifying the problems and establishing interventions for the patient’s nutritional progression.